Advances in the carbon-ceramic composites oxidation and ablation resistance: A review - Anna Didenko; Alexey Astapov (International Journal of Lightweight Materials and Manufacture)
A review and critical analysis of recent advances in the field of oxidation and ablation resistance of carbon-ceramic composite materials, which are the most promising for high temperature applications in load-bearing structures and heat-protective systems of rocket and aerospace engineering, is carried out. The focus of this study is on the behavior of Cf/UHTC, Cf/C–UHTC, Cf/SiC–UHTC, and Cf/C–SiC–UHTC composites under thermochemical interaction with oxidizing gas flows. The workability of the composites is provided by the formation and evolution of passivating heterogeneous oxide films, which are represented mainly by the refractory MeO2 phase and the glass phase modified by Me4+ cations (Me – Zr and/or Hf). The protective oxide layers slow down the mass transfer of reagents (due to the high gas density caused by the presence of phases in a viscous-fluid state) and resist mechanical erosion and denudation (due to the framework structure provided by the partial sintering of refractory phase grains). Systematization and generalization of experimental data for composites of various compositions was carried out, including consideration of fire exposure modes, realized temperatures and obtained characteristics of linear and mass ablation rates. The results of the generalization are presented in the form of tables and schematic images of microstructures of forming oxide films with layer detailing. It is demonstrated that a promising approach for improving developments is the introduction of additional refractory components, which facilitate the formation of solutions with the structure of Me1-xTixO2, Me1-yTayO2+0.5y, Me1-yNbyO2+0.5y, and/or complex compounds such as Me6Ta2O17, Me6Nb2O17 and so on during operation. The formation of oxide films leads to an increase in the fraction of viscous-fluid substances, and, consequently, to a decrease in porosity and an increase in the gas density of protective layers. The processes of melting and transporting a portion of the mass from the surface facilitate the removal of a portion of the heat from the reaction zone, which in turn reduced the overall thermal load on the composites.